Time limit at the minimum velocity of VO2max and intracyclic variation of the velocity of the centre of mass - Balonas, A.; Goncalves, P.; Silva, J.; Marinho, D.; Moreira, P.; Lima, A.; Barbosa, T.; Keskinen, K. L.; Fernandes, R.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to analyse the relationship between time limit at the minimum velocity that elicits maximal oxygen consumption (TLim-v vO2max) and intracyclic variations of the velocity of the centre of mass (dv) in the four competitive swimming techniques. Twelve elite male swimmers swam their own best technique until exhaustion at their previously determined vVO2max to assess TLim-v v O2max. The test was videotaped in the sagittal plan and the APAS Software was used to evaluate the horizontal velocity of the centre of mass (Vcm) and its intracyclic Variation (dv) per swimming technique. Results pointed out that the strokes that presented higher intracyclic variations also presented larger values of TLim. Intracyclic speed fluctuations (dv) decreased during the TLim test in the four strokes studied, probably due to fatigue.